(untitled) - Emerson, Ralph Waldo (New York, NY, 1983)
This book is the complete essays and lectures of ralph waldo emerson. It contains everything you could want from emerson, save his journals. His writing is beauty in it's truest form. What he speaks is what you have forever felt to be true. When he warns against self-distrust in self-reliance you feel that he is not only speaking to you, but speaking for you. Reading this book is not only seeing what he has written, but is a demonstration of what he has written
Keywords: American essays; 19th century